Seed and foliar inoculation with Azospirillum brasilense associated with nitrogen topdressing rates in wheat crop - Vergütz, Lucas Frederico; Tiemann, Lidiane Aline Rohr; Foletto, Mathias; Bohrz, Igor Gabriel; Vieira, Gustavo Dal Molin; Casanova, Cauê Lublo; Cossul, Vitor; Ludwig, Rodrigo Luiz (Seven Editora, 2024)
The wheat crop (Triticum aestivum) is of great importance in human and animal food, being the second largest grain production in the world. However, it is necessary to develop new technologies that increase productivity in a sustainable way, reducing the cost of implementation and operation. Thus, inoculation with growth-promoting bacteria, such as Azospirillum brasilense, appears as a viable alternative, but still requires studies for better positioning. The objective of this study was to evaluate the agronomic performance of wheat as a function of the application of Azospirillum brasilense via seed and foliar, alone and together, associated with applications of different doses of nitrogen in topdressing. The experiment was conducted in the field at the Federal Institute of Education, Science and Technology of Rio Grande do Sul, Ibirubá campus, in 2020. The experimental design was a randomized block design (DBC) with five replications per treatment, in a two-factor model, with the inoculation factors of Azospirillum brasilense (No inoculation; Seed inoculation; Inoculation via foliar and Inoculation via seed + inoculation via foliar) and nitrogen topdressing doses (0, 40, 80 and 120 kg.ha-1) using the wheat cultivar TBIO Ponteiro. The results obtained indicate that inoculation with Azospirillum brasilense via seed and foliar, alone and together, did not present significant effects on the variables evaluated, not generating results that make its use feasible, regardless of the form of inoculation, only in the variable number of ears per square meter, which showed an increase with foliar and seed + foliar inoculation. On the other hand, the highest nitrogen doses (80 and 120 kg.ha-1) showed the best results. DOI:https://doi.org/10.56238/sevened2024.023-004